Autocombustion Synthesis of Nanostructured Na2Ti6O13 Negative Insertion Material for Na-Ion Batteries: Electrochemical and Diffusion Mechanism. Issue 9 (1st January 2017) - Ghosh, Swatilekha; Mani, Allumolu Daya; Kishore, Brij; Munichandraiah, Nookala; Rao, Rayavarapu Prasada; Wong, Lee Loong; Adams, Stefan; Barpanda, Prabeer
Abstract : In the pursuit to develop practical sodium-ion batteries, safe negative insertion (anode) materials are essential. Recently, Na2 Ti6 O13 has been unveiled by conventional solid-state synthesis as a 0.85 V anode with 1-dimensional Na + diffusion pathways. Here, an energy-savvy autocombustion synthesis has been successfully implemented to produce the target compound Na2 Ti6 O13 by restricting the annealing duration within 2 h. This drastic reduction in heat-treatment time involves minimal grain-growth hence forming homogeneous nanostructured particles (∼100 nm). It benchmarks the shortest synthesis of Ti-based anodes for sodium-ion batteries. The current work describes various aspects of autocombustion route. The as-prepared compound delivers near theoretical capacity (ca. 40 mAh g −1 ) involving a Ti 4+ /Ti 3+ redox potential centered at 0.83 V (vs. Na/Na + ) with excellent reversibility. Using both experiment and bond valence site energy (BVSE) modeling, the electrochemical, Na + diffusion pathways and corresponding energy barriers have been explained.